STUDI KUALITATIF TERHADAP PERAN SERTA MASYARAKAT DAN PENGAMBIL KEBIJAKAN DALAM PROGRAM ELIMINASI FILARIASIS - Resmiwaty Resmiwaty; Made Agus Nurjana; Mujianto Mujianto (Laboratory of Anthropology Department of Cultural Science Faculty of Halu Oleo University, 2023)
A successful program depends on the participation any parts of it, such as financial, infrastructure, spirituality, including community and stakeholder participation. Similarly, the support provided ranging, such as moral, financial, facilities, and infrastucture. This study discusses the issues especially related to the Filariasis Elimination Program in Donggala Districts, Kabonga Kecil and Sabang region. Qualitative research was used in this research. Data was collected using interview and observation methods. Data analysis was conducted using qualitative approaches. This study found that the stakeholder involved in the unity of program such as surveillance, socialization, and POPM (distribution preventive drugs). The community actively participates in a series of Filariasis Elimination Programs ranging from socialization, POPM, to drug distribution. The stakeholders participate in supporting budgets, equipment, and other needs. Even the implementation of program is often considered unoptimal but overall the program has been accomplished successfully. Finally, this study can provide policy input for the authorities to plan development program, particularly Filariasis Elimination. The community is also expected to participate in the program actively. The results of study can enrich studies particularly related to community participation.